Deficits in pain perception in borderline personality disorder: results from the thermal grill illusion. Issue 10 (October 2015) - Bekrater-Bodmann, Robin; Chung, Boo Young; Richter, Ingmarie; Wicking, Manon; Foell, Jens; Mancke, Falk; Schmahl, Christian; Flor, Herta
Abstract : Abstract: It is well documented that borderline personality disorder (BPD) is characterized by reduced pain sensitivity, which might be related to nonsuicidal self-injury and dissociative experiences in patients with BPD. However, it remains an open question whether this insensitivity relies at least partly on altered sensory integration or on an altered evaluation of pain or a combination of both. In this study, we used the thermal grill illusion (TGI), describing a painful sensation induced by the application of alternating cold and warm nonnoxious stimuli, in patients with either current or remitted BPD as well as matched healthy controls. Two additional conditions, applying warm or cold temperatures only, served as control. We further assessed thermal perception, discrimination, and pain thresholds. We found significantly reduced heat and cold pain thresholds for the current BPD group, as well as reduced cold pain thresholds for the remitted BPD group, as compared with the HC group. Current BPD patients perceived a less-intense TGI in terms of induced pain and unpleasantness, while their general ability to perceive this kind of illusion seemed to be unaffected. Thermal grill illusion magnitude was negatively correlated with dissociation and traumatization only in the current BPD patients. These results indicate that higher-order pain perception is altered in current BPD, which seems to normalize after remission. We discuss these findings against the background of neurophysiological evidence for the TGI in general and reduced pain sensitivity in BPD and suggest a relationship to alterations in N -methyl- D -aspartate neurotransmission. Abstract : Supplemental Digital Content is Available in the Text.The thermal grill illusion is reduced in borderline personality disorder. This suggests that the deficits in pain perception in this group are of central origin.